Local industrial agglomerations vis-à-vis global competitive networks: marshallian notions of economic zones, innovation and territorial development - Ugalde Hernandez, Oscar (2020)
Innovation is one of the key contributions that clusters can make in driving regional and territorial development. This exhaustive postMarshallian literary review compares and contrasts the notion of innovation and explains its evolution within the context of recent theoretical approaches explaining modern industrial agglomerations and territorial development. Beginning in early 1990s and ending with the most recent intellectual contributions, this study analyzes innovation, particularly in relation to how it is employed in the cluster and how it could contribute to the development and competitiveness of clusters, territories and nations. Porter’s diamond model and its extended versions, which focus on demand and other market and factor determinants, are regarded as the intellectual catalysts for the notion of innovation in relation to clusters and territories. However, the study notes that the ambiguity and flexibility of these models led French post-Porterian writers to consider the role played by spatiality and relationality through networks, sectors and industries in sparking innovation as well as knowledge creation and diffusion. Additionally, political economy theoretical approaches, such as the helix innovation models and the Marxist-inspired semiotic analysis, have also stimulated the use of innovation as a factor of change, which spills over the influenced territories and nations. As innovation is incorporated into each of the models examined, its contribution becomes increasingly evident. The common denominator among all post-Marshallian theories is the crucial and shifting role that innovation plays as a catalyst for competitiveness and development at the cluster, territorial, national and, global levels.